Guiding New Teacher Training towards the Acquisition of a Systemic Paradigm - Barrantes-Montero, Luis Guillermo (Revista Electrónica Educare, 2015)
This paper distinguishes between positivist disciplinary paradigm, which classifies human knowledge into isolated disciplines, and systemic paradigm, which aims at integrating knowledge and an inter-and trans-disciplinarity approach. The need and convenience of preparing new professionals in the latter is discussed. An example on how to develop a training experience based on the systemic paradigm in an advanced English reading course, in a teacher-training career is also described.